IMPLEMENTATION OF INDEPENDENT CURRICULUM IN SCIENCE LEARNING AT ISLAMIC ELEMENTARY SCHOOL - Dianis Izzatul Yuanita; Khoridatul Ulum (YAYASAN CENDEKIA CITRA GEMILANG, 2025)
A great nation has numerous people and quality human resources, which education provides. The curriculum is an important part of any educational institution. in an educational setting. Implementation is the term. Implementation is usually a goal-oriented activity. The Minister of Education launched the autonomous curriculum in 2022 to address Indonesia's learning crisis. to solve Indonesia's learning crisis. Science in primary school is intended to help kids understand their surroundings. Students can understand the environment and social standards. This study examines MI Islamiyah's scientific curriculum teaching and learning. This descriptive-qualitative research uses data from observations, documentation, and interviews with the madrasah head, class teachers, and vice-head for curriculum and research directly following classroom activities. Data from observations and interviews shows that an autonomous science curriculum is most significant. An independent scientific curriculum has been efficiently implemented at MI Islamiyah Banjarmlati, Kediri City's 4th grade. Teachers must keep innovating to make learning interesting.